EXPERIMENTAL INVESTIGATION ON THE CONDENSATION HEAT TRANSFER AND PRESSURE DROP CHARACTERISTICS OF R134A AT HIGH MASS FLUX CONDITIONS DURING ANNULAR FLOW REGIME INSIDE A VERTICAL SMOOTH TUBE - Dalkilic, Ahmet Selim; Laohalertdecha, Suriyan; Wongwises, Somchai (AMER SOC MECHANICAL ENGINEERS, 2009)
This paper presents an experimental investigation on the co-current downward condensation of R134a inside a tube-in-tube heat exchanger. The test section is a 0.5 m long double tube with refrigerant flowing in the inner tube and cooling water flowing in the annulus. The inner tube is constructed from smooth copper tubing of 9.52 mm outer diameter and 8.1 mm inner diameter. The condensing temperatures are between 40 and 50 degrees C, heat fluxes are between 9.78 and 50.69 kW m(-2). The temperature difference between the saturation temperature of refrigerant and inlet wall varies between 1.66-8.94 degrees C. Condensation experiments are done at mass fluxes varying between 340 and 456 kg m(-2)s(-1) while the average qualities are between 0.76-0.96. The quality of the refrigerant in the test section is calculated considering the temperature and pressure measured from the test section. The pressure drop across the test section is directly measured by a differential pressure transducer. The average experimental heat transfer coefficient of the refrigerant is calculated by applying an energy balance based on the energy transferred from the test section. Experimental data of annular flow are examined such as the alteration of condensation heat transfer coefficient with the vapor average quality and temperature difference respectively according to different mass fluxes and condensing temperatures. The relation between the heat flux and temperature difference, besides this, the relation between the condensation heat transfer coefficient and condensing pressure are shown comparatively and the effects of mass flux and condensation temperature on the pressure drop are also discussed. The efficiency of the condenser is considered comparing with various experimental data according to tested condensing temperatures and mass fluxes of refrigerant. Some well known correlations and models of heat transfer coefficient were compared to show that annular flow models were independent of tube orientation provided that annular flow regime exists along the tube length and capable of predicting condensation heat transfer coefficient in the test tube.
Keywords: 2-PHASE FRICTION FACTOR; SURFACE CONDENSATION; DOWNWARD FLOW; Engineering